Genetic Differentiation of the Broodstocks of Black Ear Catfish (Panggasius Larnaudii Bocourt, 1866) - Tangprakhon, Thipsuda (2006)
Black ear catfish, Pangasius larnaudii Bocourt, 1866 is one of the dominant food fish and commercially important pangasiid species in Thailand. The Thai Department of Fisheries (DoF) has engaged in breeding programmes of this fish for aquaculture as well as for restocking natural waterways for enhancing fish production. Presently, the P. larnaudii fingerlings are produced from ten DoF hatcheries with the broodstocks either from the wild (P0), F1 or F2 progenies some of which were transferred among the fisheries. Little is known about the history of the stock as no record was properly kept. Thus, this study was undertaken to determine the genetic variation, relationships and differentiation among ten of DoF hatchery populations and three natural populations from rivers using microsatellite markers. Four microsatellite primer pairs, namely PSP-G507, PSP-G513, PSP-G576, and PSP-G579 were used in this study. DNA was extracted from individual fin clips using a single tube extraction procedure for fish blood with some modifications. This procedure was used to extract DNA with good quality for PCR amplification. A total of 27 primer pairs were used to screen and optimize microsatellite loci for studying genetic variation in P. larnaudii, of which only four microsatellite primer pairs were selected for further analysis. The results indicated a wide range of genetic variability among the populations. The average number of alleles per locus ranged from 2.8 to 15.8 and the observed heterozygosity ranged from 0.319 to 0.864. A wide range of allele frequencies were observed over all the loci, with the highest in the Uthaitani population, followed by the Mekong population while the lowest was found in the Chainat population. The average genetic distance (DT) and genetic differentiation (FST) between populations ranged from 0.120 to 0.539 and 0.013 to 0.349, respectively. The UPGMA dendrogram showed that the populations of P. larnaudii are clustered into two main groups: the Thai DoF hatchery and the natural river groups. Most of the populations from the DoF hatcheries were distinctly separated from the natural populations. In turn, the populations from the ten DoF hatcheries can be separated into four subgroups: Subgroup I consists of Lopburi and Uhaitani, Subgroup II consists of Ubonratchatani, Srisaket and Nakhonpanom, Subgroup III consists of Yasothon, Surin, Buriram and Chainat while Roi-ed is the only member of Subgroup IV. Besides, the populations of the DoF hatcheries can also be categorized into two separate regions; the middle and the northeastern regions. The Lopburi and Uthaitani populations represented the middle group and the rest represented the northeastern group. The Chainat population was included in the northeastern group, despites of its actual location, indicating that the stock was transferred from the Yasothon hatchery. The small genetic differentiation among the populations of the northeast group suggested that there were closely related predecessors among their broodstocks. From this study, the occurrence of inbreeding effects was more obvious in the populations of the DoF hatcheries than in the natural rivers. The small genetic differentiation among all the populations indicated that there was migration among the populations of P. larnaudii in Thailand. The findings from this study are relevant and useful to the Thai DoF hatchery managers for improving the efficiency of breeding programmes and to maintain the genetic integrity of P. larnaudii in Thailand. This study recommends that stocks must not be transferred among hatcheries outside the region of origin of a particular population in order to maintain its genetic integrity